tudy of Kalina Cycle System 11 and 34 as Geothermal Power Plants with Brine Temperature of 100â200Â°C - Widodo, Rahmat
Indonesia is a country that has an area of 1,910,931 km2 with a population of 255,182,144 in 2010. This causes Indonesia to have high electricity demand, so there must be an increase in power plant capacity. One that can be utilized as a power plant in Indonesia is geothermal energy with a potential power of 29,544 MW. One of the solutions to increase efficiency in the use of geothermal energy is Kalina cycle by using a mixture of ammonia and water. The non-constant boiling temperature of the mixture fluid can lead to an increase in efficiency. In this research, optimization process was done in Kalina cycle system 11 and 34 with Cycle Tempo. The optimization process was done by using brine that has temperature of 100–200°C. The result of optimization was net power per unit mass flow of brine in each Kalina cycle system at brine temperatur of 100–200°C. The two systems were then compared to determine which system that can produce the largest net power per unit mass flow of brine. Optimization shows that the Kalina cycle system 34 is good at brine temperature of 100–150°C, while the Kalina cycle system 11 is good at brine temperature of 155–200°C. The Kalina cycle 34 system that use brine temperature of 130-150°C produces dry vapor condition in ammonia-water solution before entering the separator. This causes a separator and a heat exchanger can be removed from the system, so that fewer components are used.